Uji Aktivitas Antifungi Sediaan Sampo Ekstrak Etanol Bawang Merah (Allium cepa L.) Terhadap Pityrosporum ovale - Rahmiati Rahmiati; Megawati Butar-butar; Helen Anjelina Simanjuntak (Herbal Medicine Journal, 2021)
Onion which is a species Alium cepa L. is the name of the plant of the family Lilliaceae. This research was conducted to get antidandruff shampoo of extract ethanol onion (Allium cepa L.) that has the best antifungal activity. This research method used an experimental method. The result of this study prove that the etanol extract of onion (Allium cepa L.) can be formulated as antidandruff shampoo that meets the requirements according to standard of Indonesian National Standard (SNI). The results of antifungal activity test showed that shampoo with a concentration of 5% with a diameter of 34.25 mm had the best antifungal activity followed by 2,5% shampoo with a diameter of 30,5 mm and a shampoo concentration of 1% with a diameter of 27,25 mm to inhibit the growth of Pityrosporum fungi ovale. Data analysis of antifungal test result was done by One Way Anova statistical test. The results showed that there were significant differences between the antidandruff shampoo onion (Allium cepa L.) extract 1%, 2,5%, and 5% concentration.